Cardiac involvement in Scorpion envenomation: A review of literature - Mitrakrishnan Rayno Navinan; Dilushi Rowena Wijeyaratne (Majalah Kardiologi Indonesia)
Scorpion envenomation (SE) causes cardiac complications. Pubmed, Scielo, Embase and google scholar were searched using the keywords scorpion: cardiac, heart, arrhythmia, electrocardiograph and myocarditis in the abstract or text. 112 were selected. Cardiotoxicity can occur within 2 hours of SE and include hyper/hypotension, arrhythmias, myocarditis and heart failure. The postulated mechanisms are autonomic storm, inflammation, direct venom toxicity and metabolic derangement. Haematological and biochemical derangement suggests increased severity. Cardiac biomarkers, electrocardiography and transthoracic echocardiography helps detect cardiotoxicity and guide management. Early use of antivenom and/or alpha-adrenergic blockade may prevent or reverse cardiotoxicity. Hypertension is best managed alpha-adrenergic blockers. Arrhythmias are usually transient. Cardiovascular complications of SE are associated with morbidity and mortality. A clear consensus on the indication and utilization of antivenom administration in cardiac involvement SE are needed.